К решению проблемы динамического деформирования пьезоэлектрических многослойных пластин на основе гибридного ВКБ-Галеркин метода - Грищак, В.З.; Ганилова, О.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper deals with the problem of the behavior of a symmetric orthotropic piezoelectric sandwich plate subjected to the dynamic normal loading q(x, y, t) taking into consideration the damping coefficient variable in time. A hybrid WKB-Galerkin method is applied to solve the problem. The results obtained are compared with numerical results.